2011
DOI: 10.1016/j.apm.2011.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Transient analysis of thermo-elastic waves in thick hollow cylinders using a stochastic hybrid numerical method, considering Gaussian mechanical properties

Abstract: a b s t r a c tThis article attempts to study the stochastic coupled thermo-elasticity of thick hollow cylinders subjected to thermal shock loading considering uncertainty in mechanical properties. The thermo-elastic governing equations based on Green-Naghdi theory (without energy dissipation) are stochastically solved using a hybrid numerical method (combined Galerkin finite element and Newmark finite difference methods). The mechanical properties are considered as random variables with Gaussian distribution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[18] introduced memory‐dependent derivative (MDD), instead of fractional calculus, into the Lord and Shulman (LS) generalized thermoelasticity and established a new memory‐dependent LS model. Transient analysis of thermo‐elastic waves in thick hollow cylinders using a stochastic hybrid numerical method was developed by Hosseini and co‐workers [19]. Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…[18] introduced memory‐dependent derivative (MDD), instead of fractional calculus, into the Lord and Shulman (LS) generalized thermoelasticity and established a new memory‐dependent LS model. Transient analysis of thermo‐elastic waves in thick hollow cylinders using a stochastic hybrid numerical method was developed by Hosseini and co‐workers [19]. Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hosseini et al [74] analyzed thermoelastic waves in a thick hollow cylinder for which some material properties are independently random. The statistics of temperature, stresses, and displacement were obtained by combining a hybrid numerical method, which consists of the Galerkin FEM and the Newmark FDM, and Monte Carlo simulation.…”
Section: Case Of Random Materials Propertiesmentioning
confidence: 99%
“…It is shown that thermal properties have no effect on the circumerential SH wave and the thermoelasticity has very limited effects on the other circumferential modes. In 2011, a work on the randomness of thermoelasticity wave in thick hollowed cylinder was reported [15]. They analytically studied the thermal and mechanical waves using theory of coupled thermoelasticity without energy dissipationbased on Green-Naghdi model.…”
Section: Introductionmentioning
confidence: 99%